Accounting for non-accounting students - Dyson, J. R. (John R.); Franklin, Ellie (Harlow: Pearson, 2001)
"Picking up accounting as a language and as a skill will add credibility to your CV and enhance your employability. Any job role you may be involved with - from an HR manager, to investment banker, to a self-employed musician - they all require, and are done better with, a basic grasp and understanding of accounting to be able to make financially sound decisions on a daily basis. Warren Buffet is an example - not an accountant - but making a good use of accounting in his investment and business dealings to notable success"--
Includes bibliographical references and index.
Keywords: Accounting